DYNAMICS OF BONE FORMATION AND OSTEORESORPTION MARKERS IN PATIENTS WITH POSTOPERATIVE MANDIBULAR BONE DEFECTS - Khattou, V.V.; Ivanytska, O.S.; Havryliev, V.M.; Buhanchenko, O.P.; Boyko, I.V.; Lokes, K.P.; Avetikov, D.S. (World of Medicine and Biology, 2023)
The defect that appears after a tooth extraction leads to remodeling of bone tissue. The processes of remodeling and mineralization of the newly formed bone are affected by substances with an antioxidant effect, among which are quercetin and placenta cryoextract. The study involved 90 procedures in which tooth extraction was performed: using placenta cryoextract (group 1), combination of placenta cryoextract with quercetin (group 2) and standard treatment protocol (group 3). The content of osteocalcin and matrix metalloproteinase-8 in blood serum was determined. The formation of a postoperative defect in bone tissue was accompanied by antagonistic changes in the content of osteocalcin (due to its increase) and MMP-8 (due to its decrease) in the blood serum and oral fluid of patients, which characterizes the activation of bone tissue resorption processes at earlier times and bone formation at later times.